Genetic Factors Underlying Single Fiber Quality in A-Genome Donor Asian Cotton (Gossypium arboreum) - Iqbal, Muhammad Shahid; Tang, Shurong; Sarfraz, Zareen; Iqbal, Muhammad Sajid; Li, Hongge; He, Shoupu; Jia, Yinhua; Sun, Gaofei; Pan, Zhaoe; Xiaoli, Geng; Mahmood, Abid; Ahmad, Saghir; et al. (Frontiers in Genetics, 2021)
The study of A-genome Asian cotton as a potential fiber donor in Gossypium species may offer an enhanced understanding of complex genetics and novel players related to fiber quality traits. Assessment of individual fibers providing classified fiber quality information to the textile industry is Advanced Fiber Information System (AFIS) in the recent technological era. Keeping the scenario, a diverse collection of 215 Asiatic cotton accessions were evaluated across three agro-ecological zones of China. Genome-Wide Association Studies (GWAS) was performed to detect association signals related to 17 AFIS fiber quality traits grouped into four categories viz; NEPs, fiber length, maturity, and fineness. Significant correlations were found within as well as among different categories of various traits related to fiber quality. Fiber fineness has shown a strong correlation to all other categories, whereas these categories are shown interrelationships via fiber-fineness. A total of 7,429 SNPs were found in association with 17 investigated traits, of which 524 were selected as lead SNPs. In the vicinity of lead SNPs, 300 differentially expressed genes in various tissues/development stages were identified as candidate genes. This compendia connecting trait-SNP-genes may allow further prioritization of genes in GWAS loci to enable mechanistic studies. These identified QTNs may prove helpful in fiber quality improvement in Asian cotton through marker-assisted breeding as well as in reviving eroded genetic factors of G. hirsutum via introgression breeding.